The Role of Motivation and Work Discipline in Improving Employee Performance at the Cikande District Office, Serang Regency - Saleh, Muhammad; Hidayat, Ardi (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of motivation and work discipline on employee performance at the Cikande District Office, Serang Regency. The population and sample of this study were employees at the Cikande sub-district office totaling 31 people. Data Collection Techniques Used In This Research In The Form Of Questionnaire Consisting Of Five Choices With Likert Scale, Documentation Study And Interview (Interview). While the data analysis technique in this study uses the classical assumption test, multiple linear regression, t test, F test, and the coefficient of determination. The results of the study show that the variables of motivation and work discipline have a positive and significant effect on employee performance at the Cikande District Office, Serang Regency. Based on the partial test, it is known that motivation has a positive and significant effect on employee performance, while work discipline has no effect and is not significant on employee performance